Vitamin D Receptor TaqI Polymorphism Is Associated With Reduced Follicle Number in Women Utilizing Assisted Reproductive Technologies - Reginatto, Mila W.; Pizarro, Bartira M.; Antunes, Roberto A.; Mancebo, Ana C. A.; Hoffmann, Luísa; Fernandes, Pâmela; Areas, Patrícia; Chiamolera, Maria I.; Silva, Rosane; Souza, Maria do Carmo Borges de; Bloise, Enrrico; Ortiga-Carvalho, Tânia M. (Frontiers in Endocrinology, 2018)
Purpose: Calcitriol, or 1,25-hydroxycholecalciferol, is the active form of vitamin D. It binds and activates vitamin D nuclear receptor (VDR). Infertility and defective folliculogenesis have been observed in female vdr-knockout mice; however, whether VDR polymorphisms affect human ovarian responses to controlled ovarian stimulation (COS) remains unclear. We hypothesized that VDR polymorphisms are associated with infertility and COS responses. Thus, we evaluated the association between the TaqI, BsmI and FokI VDR polymorphisms and ovarian responses in women undergoing COS. Methods: In this study, we recruited a control group (n=121) comprising volunteers with a history of natural conception and a second group of women undergoing COS (n=70). TaqI, BsmI and FokI genotyping was performed via restriction fragment length polymorphism analysis or TaqMan qPCR and Sanger sequencing. Intrafollicular 25(OH)D contents were measured in follicular fluid collected from COS patients during oocyte retrieval. Ovarian response parameters were obtained from patient medical records. Results: There were no significant differences in the genotype frequencies of VDR polymorphisms (TaqI, BsmI and FokI) between the control and COS groups. However, the allelic frequency of TaqI (C allele) was significantly lower in the COS group than in the control group (p=0.02). Follicle number but not oocyte number was lower in patients with TaqI polymorphic (TC/CC) genotypes (p=0.03). Importantly, the ratio between the number of follicles retrieved and intrafollicular estradiol concentrations was higher in patients with the TC/CC TaqI genotypes (p<0.02). Conclusion: We identified an association between the VDR TaqI polymorphism and reduced follicle number in women undergoing COS, suggesting that VDR signaling affects the ovarian response to stimulation via unknown mechanisms.